TP53 mutations in functional corticotroph tumors are linked to invasion and worse clinical outcome - Perez-Rivas, Luis Gustavo; Simon, Julia; Albani, Adriana; Tang, Sicheng; Roeber, Sigrun; Assie, Guillaume; Deutschbein, Timo; Fassnacht, Martin; Gadelha, Monica R.; Hermus, Ad R.; Stalla, Guenter K.; Tichomirowa, Maria A.; et al. (Acta Neuropathologica Communications, 2022)
Corticotroph macroadenomas are rare but difficult to manage intracranial neoplasms. Mutations in the two Cushing’s disease mutational hotspots USP8 and USP48 are less frequent in corticotroph macroadenomas and invasive tumors. There is evidence that TP53 mutations are not as rare as previously thought in these tumors. The aim of this study was to determine the prevalence of TP53 mutations in corticotroph tumors, with emphasis on macroadenomas, and their possible association with clinical and tumor characteristics. To this end, the entire TP53 coding region was sequenced in 86 functional corticotroph tumors (61 USP8 wild type; 66 macroadenomas) and the clinical characteristics of patients with TP53 mutant tumors were compared with TP53/USP8 wild type and USP8 mutant tumors. We found pathogenic TP53 variants in 9 corticotroph tumors (all macroadenomas and USP8 wild type). TP53 mutant tumors represented 14% of all functional corticotroph macroadenomas and 24% of all invasive tumors, were significantly larger and invasive, and had higher Ki67 indices and Knosp grades compared to wild type tumors. Patients with TP53 mutant tumors had undergone more therapeutic interventions, including radiation and bilateral adrenalectomy. In conclusion, pathogenic TP53 variants are more frequent than expected, representing a relevant amount of functional corticotroph macroadenomas and invasive tumors. TP53 mutations associated with more aggressive tumor features and difficult to manage disease.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Corticotroph; Cushing’s disease; Macroadenomas; TP53; USP8